The Impact of the French Revolution on Convergence Ottoman-British Politician (1789-1815) - Nader Qawasmh, Mohammad; Zaid AL-Shnaq, Abdal Majeed (Dirasat: Human and Social Sciences, 2022)
This study examines the impact of the French Revolution on Convergence the Ottoman-British politics in the period from 1789 to 1815. where it reviews the status of both the Ottoman Empire and the state in that period, showing the nature and development of the relations that arose between the two parties. The importance of the study lies in its attempt to address the political developments that contributed to the fluctuation of the mutual political relations between the Ottoman Empire and Britain during the study period. The study aimed to shed light on the role of the Ottoman policy in exploiting the principle of conflict of interests; To maintain the integrity of its territories from any European aggression, and to avoid any political situation that might involve it in the European conflict resulting from the Napoleonic wars on the European continent. The study concluded with a set of results, the most prominent of which were: Showing the importance of the diplomatic role in managing political events in that critical period, and showing the extent of the flexibility of the Ottoman Empire in dealing with emerging political changes, and its success in exploiting the principle of conflict of interests between the great powers to lead to political gains.